Comportamiento productivo de la sandía citrullus lannatus l variedad peackoc wr 124 sometida a diferentes sistemas de poda - Lomas Rosales, Holger Alberto (2017)
The present work had as an objective to analyze the "PRODUCTION BEHAVIOR OF THE WATERMELON (Citrullus lannatus L.) PEACKOC WR124 VARIETY SUBJECT TO DIFFERENT PODA SYSTEMS", for which it was established as a general objective to evaluate the productive capacity in quantity and quality of Fruits of the Peackoc WR-124 watermelon subjected to different pruning systems in the rainy season in an open field seeding system, for which two specific objectives were established: (1) determine the best pruning system in watermelon Peackoc WR- 124 on fruit production, and (2) to evaluate the yield quality of the Peackoc WR-124 watermelon under different types of pruning. The field phase was executed in the Palmales parish of the Arenillas canton, the sowing was executed on a soil of the order Inseptisol with a height of 74 m asl, with a textural estimate Franca clayey in the first 20 cm of depth. The sowing was direct to the established sites within the different experimental units according to the sketch of the field design based on the Design of Complete Blocks at Random, where four treatments were formed: (without pruning, Primary Guide, a secondary guide and a Tertiary guide) with three blocks of replicates, running during the month of February to May 2017 and evaluating the number of plants that arrived until the harvest and the amount of fruits that were obtained by plants within the useful plot, where each Fruit were taken measures of polar length and equatorial diameter, were also weighed and extrapolated to fruit yield and tons per hectare in each of the treatments, as well as established to the commercial classification established by merchants of the locality, of which Were formed into two commercial categories, the first fruits and the second fruits that equate to two fruits accounted for or as a first, were also considered as rejection those who did not have their morphological characteristics commercial, deformed, mechanical or physiological damage. Regarding the number of plants that reached the harvest as the production of fruits per hectare there was a statistical difference marked the treatments with pruning different were statistically on the treatment where it was not pruned, whereas there was no statistical difference in the production of fruits For plants, the weight and diameter of fruit were classified into two groups where the highest average had it where it was worked with a single secondary guide, while the yield in tons in unit of hectare and length of fruit was for a single secondary guide who conformed A single statistical group different from their peers; In the production of fruits with commercial quality and rejection, it was established that the pruning systems exceeded notably where the plant was not pruned, where the treatment was emphasized where a single tertiary guide was used. It should be noted that only one harvest could be made, since the spoilage of the plants due to the heavy rainfall during their cycle did not allow to produce more harvests, that the demand for this type of product was very high, since there is no income of this type of fruit from Peru.